When natives meet immigrants in public and private housing markets - Li, Xiaolu (2020)
Many countries provide inexpensive public housing to citizens and residents, whereas foreigners are only allowed to purchase relatively scarce and expensive private housing. Undoubtedly, the growth in native (foreign) population size will directly contribute to higher public (private) housing price, and indirectly induce higher private (public) housing price via general equilibrium effects. The question is how to quantitatively evaluate the magnitude of each impact. To address this issue, we propose a dynamic general equilibrium framework with heterogeneous native and foreign agents interacting in both public and private housing markets. Natives can upgrade from public to private housing over their lifetime. We also allow the option for foreigners to choose to obtain permanent residency and then compete with natives in the public housing market. We calibrate the model into the Singapore economy between 1993 and 2015. The model accounts for about 85.7% of private housing price growth and 46.2% of public housing growth in the data. The decomposition exercises suggest that native population growth can generate about 67.0% of private housing price growth, while the growth of the foreign population can generate about 7.05% of public housing price growth. Finally, when borrowing is not allowed, the demand for private housing decreases, and this pushes down the private housing price.